Business Partnership as an Element of Building Customer Value - Walasek, Robert; Karolewska-Szparaga, Małgorzata; Starzyńska, Dorota (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The main aim of the article is to try to characterise the impact of a business partnership on creating value (CVA – customer value added), based on mutual collaboration in the supply chain. The study looks at the aspect of creating added value through activities that create benefits to supply chain partners, playing an important role in creating customer loyalty, and what follows – the competitiveness of the company. Research Design & Methods: The study used the desk research method in the field of statistical data analysis, the comparative analysis method and the method of critical analysis of literature on the subject. To obtain the primary data, a survey technique was used, the research tool of which was a research questionnaire distributed electronically (CASI) in the form of a survey questionnaire. The survey method was supplemented by the method of telephone interviews (CATI) and face-to-face interviews (CAPI). Findings: The research shows that establishing partnerships, especially with customers, is broadly reflected in the benefits that all entities forming a common supply chain obtain. These benefits have not only a social dimension through building partnerships, but also an economic one. As research shows, participation in a partnership has a direct impact on building long-term customer satisfaction, which naturally translates into benefits for the entire supply chain. When deciding to create partnerships with customers, enterprises try to minimise the risk of failure, and their greatest fears do not concern the aspects of the internal environment, but the economic and social situation of the world. Implications / Recommendations: Currently, the creation of a business partnership within the framework of cooperation is becoming the basis for building the competitiveness of enterprises in the market. The effects of such cooperation are to a large extent synergy effects, leading to the development and growth of potential based on the cooperation of entities co-creating supply chains, including: suppliers, customers, manufacturers and intermediaries. In the near future, taking into account the difficult conditions of competing in a complex and dynamic socio–political environment, it will be extremely important for enterprises to intensify activities to build long-term partnerships based on trust and mutual benefits with contractors (suppliers, customers, cooperators). In this situation, business partnership will be an effective tool in the fight for customers, and at the same time it will be conducive to building the company’s competitiveness in a turbulent market. Contribution: The contribution of our research to the current scientific discourse consists of identifying the basic relationships between building partnerships in the supply chain and creating added value for the customer, which in the perspective of the volatility of the environment allows enterprises to achieve relative economic stability. This gives managers responsible for strategic decisions some guidance on how to efficiently balance the economic goals of the company and social and environmental goals related to customer satisfaction.